A cubane-type manganese complex with H2O oxidation capabilities. Issue 9 (1st July 2020) - Tandon, Swetanshu; Soriano-López, Joaquín; Kathalikkattil, Amal C.; Jin, Guanghua; Wix, Paul; Venkatesan, Munuswamy; Lundy, Ross; Morris, Michael A.; Watson, Graeme W.; Schmitt, Wolfgang
Abstract : A Mn coordination cluster whose core shares some features with the natural oxygen evolving complex provides a bio-inspired complex that promotes catalytic H2 O oxidation at neutral pH value. Abstract : We report the synthesis and characterisation of [Mn8 K2 O4 (OH)2 ((CH3 )3 CCOO)16 (CH3 CN)2 ] whose cluster core shares some features with the oxygen evolving complex (OEC), the natural water oxidation catalyst. Importantly, this complex provides a bio-inspired complex that promotes catalytic H2 O oxidation at neutral pH value.